Boas práticas de desenvolvimento de novos produtos digitais: o caso de uma instituição financeira cooperativa - Bervian, Cassiano José (Universidade do Vale do Rio dos Sinos, 2020)
This study sought to meet the general objective of proposing a model of dimensions to identify good practices in the development of new digital products for a Cooperative financial institution. The survey was conducted at one of the largest Cooperative financial institutions in Brazil. In accordance with Sicredi's Corporate Strategy, the company created and developed the digital account. The research had a qualitative stage with a semi-structured interview with professionals developing new digital products, in order to verify which practices and dimensions were used. The methodology used to develop the research was the Design Science Recearch. The constitution of the model was based on the perception of the “specialists” in the development of new digital products. The main findings of the study were the following: (i) identification of 87 good practices, among the 187 sent; (ii) Emergence of 27 new digital practices used by specialists; (iii) constitution of the model consisting of ten dimensions.
Keywords: Sicredi; Desenvolvimento de novos produtos digitais; Boas práticas; Dimensões de desenvolvimento de novos produtos digitais; Woop; Development of new digital products; Best practice; Dimensions of new digital product development; NPD; ACCNPQ::Ciências Sociais Aplicadas::Administração